Do something for nothing : seeing beneath the surface of homelessness, through the simple act of a haircut - Coombes, Joshua (Akashic Books, 2021)
"In 2015, while working at a London hair salon, Joshua Coombes took to the streets with his scissors to build relationships with people sleeping rough in the capital and began posting transformative images on social media to amplify their voices - #DoSomethingForNothing was born. Featuring never-before-seen photographs and all-new writing, this book explores themes of love, acceptance, shame, and perseverance, while inviting us to see ourselves in one another and dissolve the negative stigmas surrounding homelessness.--